Photoluminescence of Pentavalent Uranyl Amide Complexes - Ortu, Fabrizio; Randall, Simon; Moulding, David J.; Woodward, Adam W.; Kerridge, Andrew; Meyer, Karsten; la Pierre, Henry Storms; Natrajan, Louise S. (Journal of the American Chemical Society, 2021)
Pentavalent uranyl species are crucial intermediates in transformations that play a key role for the nuclear industry and have recently been demonstrated to persist in reducing biotic and abiotic aqueous environments. However, due to the inherent instability of pentavalent uranyl, little is known about its electronic structure. Herein, we report the synthesis and characterization of a series of monomeric and dimeric, pentavalent uranyl amide complexes. These synthetic efforts enable the acquisition of emission spectra of well-defined pentavalent uranyl complexes using photoluminescence techniques, which establish a unique signature to characterize its electronic structure and, potentially, its role in biological and engineered environments via emission spectroscopy.
CRIS-Team Scopus Importer:2021-09-10